Debate on the Economic and Monetary Integration in Europe: the Case of Portugal - Andrade, João Sousa (DEMO, 2017)
Th e European economic and monetary integration of Portugal should be analyzed from a historical perspective, taking into account not only economic but also political aspects. Despite its colonial heritage, Portugal is a country of emigrants in which Europe holds a very important part. Portuguese people have a European feeling they do not forget a dictatorship that has lasted almost half a century. The incomes of Portuguese are nowadays much higher as also the level of fixed capital - especially in infrastructure - and human capital than before European integration. The recent economic problems of the Portuguese economy are the result of imbalances that developed during the years aft er the Democratic Revolution. The absence of more appropriate policies for a monetary zone with a fi xed exchange rate and with financial shocks caused by the reduction of interest rates and the massive entry of structural funds is responsible for the poor performance of the Portuguese economy aft er 2002. At present the banking crisis and public debt do not allow the exit of the Euro. But in spite of this constraint Portuguese governments and the great majority of the political parties envisage a deeper integration in the monetary union.(original abstract)